Review of the hymenopteran fauna of New Caledonia with a checklist of species - Jennings, John T.; Krogmann, Lars; Burwell, Chris (Zootaxa, 2013)
The hymenopteran fauna of New Caledonia is reviewed and compared with that of Australia and New Zealand, as well as other islands in the south-west Pacific. In conclusion, several different scenarios (e.g., recent dispersal events and radiations) can be used to explain the extant distribution of New Caledonian Hymenoptera. A detailed checklist of 409 species and subspecies of Hymenoptera of New Caledonia is provided, along with estimates of the undescribed fauna, and a summary of the general biology of the families represented in the region.